Bilingual youth : Spanish in English-speaking societies - Potowski, Kim; Rothman, Jason (Studies in bilingualism, 2011)
The present volume represents a variety of portraits of what happens when families attempt to raise children in Spanish while living in English-speaking societies. Aided by the foregrounding chapter by Suzanne Romaine about language and identity and the afterword by Carol Klee that ties together many issues brought up throughout the collection, the reader gains a more complete understanding of the variables that contribute to Spanish bilingualism in English-speaking societies, and by extension a more complete understanding of the dynamic nature of bilingualism in general. This volume, the firs.